2021
DOI: 10.1021/acs.jafc.0c05667
|View full text |Cite
|
Sign up to set email alerts
|

Nerolidol, a Sesquiterpene from the Essential Oils of Aromatic Plants, Attenuates Doxorubicin-Induced Chronic Cardiotoxicity in Rats

Abstract: The clinical usage of doxorubicin (DOX), a potent anthracycline antineoplastic drug, is limited due to its cardiotoxicity. The aim of this study was to assess the possible cardioprotective effects of nerolidol (NERO) in a rat model of DOXinduced chronic cardiotoxicity and the underlying molecular mechanisms. DOX (2.5 mg/kg) was injected intraperitoneally once in a week for 5 weeks to induce chronic cardiotoxicity in male albino Wistar rats. The rats were treated with NERO (50 mg/kg, orally) 6 days a week for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…61 Some studies have proved that Nrf2 can improve cardiac function injury and structural changes in mice by regulating oxidative stress. 62,63 CAT, MDA and T-SOD are important indicators of oxidative stress. 64,65 NQO1, SOD2, SOD3 and CAT serve as markers for antioxidant capacity and catalytic removal of peroxides.…”
Section: Papermentioning
confidence: 99%
“…61 Some studies have proved that Nrf2 can improve cardiac function injury and structural changes in mice by regulating oxidative stress. 62,63 CAT, MDA and T-SOD are important indicators of oxidative stress. 64,65 NQO1, SOD2, SOD3 and CAT serve as markers for antioxidant capacity and catalytic removal of peroxides.…”
Section: Papermentioning
confidence: 99%
“…The PI3K-AKT signaling pathway plays a vital role in regulating the muscle hypertrophy and atrophy response (77). Studies have revealed that DOX inhibited PI3K-AKT activity both in vivo and in vitro (79,(88)(89)(90). PI3K, a lipid kinase family transducing receptor tyrosine kinase signaling, is aberrantly upregulated in human cancers frequently (91).…”
Section: Pi3k and Aktmentioning
confidence: 99%
“…For example, Chen et al found that total flavonoids stimulated PI3K-AKT and attenuated DOX-induced HW loss, while inhibition of PI3K-AKT abrogated the protection of total flavonoids against DIC (97). Meeran et al revealed that nerolidol, a sesquiterpene from the essential oils of aromatic plants, alleviated DOX-induced cardiac atrophy possibly via the PI3K-AKT pathway (88). Intriguingly, both upregulation and downregulation of PI3K-AKT triggered by DOX has been reported (98,99).…”
Section: Pi3k and Aktmentioning
confidence: 99%
“…The most accepted mechanism includes increased oxidative stress due to an excessive formation of reactive oxygen species (ROS). ROS generation in Dox-induced cardiotoxicity is related to changes in myocardial energy metabolism and mitochondrial dysfunction, impairment in iron handling, and the presence of nitric oxide synthase [ 6 , 7 ]. Moreover, Dox deactivates antioxidant substances such as glutathione peroxidase, superoxide dismutase, and catalase [ 1 ].…”
Section: Introductionmentioning
confidence: 99%